Mortality and Revision Surgery Are Increased in Patients With Parkinson's Disease and Fractures of the Femoral Neck. Issue 10 (October 2015) - Karadsheh, Mark S.; Weaver, Michael; Rodriguez, Kenneth; Harris, Mitchel; Zurakowski, David; Lucas, Robert
Abstract: Background: Patients with Parkinson's disease are at increased risk for falls and associated hip fractures as a result of tremor, bradykinesia, rigidity, and postural instability. The available literature is limited and conflicting regarding the optimal surgical treatment and risk for postoperative complications and mortality in this unique patient population. Questions/purposes: We asked: (1) Is there a difference in mortality after surgical treatment of hip fractures in patients with Parkinson's disease compared with similar patients with hip fractures without Parkinson's disease? (2) Does Parkinson's disease lead to a higher rate of reoperation after operative treatment of femoral neck fractures? (3) Does Parkinson's disease lead to a higher rate of dislocation after hemiarthroplasty for displaced femoral neck fractures, and (4) does the operative approach affect dislocation rates? Methods: In this case‐controlled study, we retrospectively reviewed 141 patients with a diagnosis of Parkinson's disease and a fracture of the femoral neck. Each patient with Parkinson's disease was matched with two control patients (n = 282) without Parkinson's disease stratified by age, sex, American Society of Anesthesiologists classification, and fracture type (nondisplaced/displaced). Clinical outcomes included mortality after surgical intervention, rate of reoperation, dislocation events after hemiarthroplasty, and the rate of failure after internal fixation for nondisplaced fractures. Results: The median survival time of the patients with Parkinson's disease after fracture was 31 months (95% CI, 25‐37 months) compared with 45 months (95% CI, 39‐50 months) in our control group (p = 0.007). The rate of reoperation for displaced and nondisplaced fractures was higher in the Parkinson's disease group compared with the control group (11% versus 4%; p = 0.005). Failure of fixation for patients treated with internal fixation of nondisplaced femoral neck fractures was significantly higher in the Parkinson's disease group compared with our control group (22% versus 5%; p = 0.01). Dislocation rates after hemiarthroplasty were significantly higher in the Parkinson's disease group compared with the control group (8% versus 1%; p = 0.003). Patients treated with a hemiarthroplasty through an anterolateral approach had a significantly lower dislocation rate compared with those treated with a posterior approach (2% versus 15%; p = 0.002). Conclusions: Parkinson's disease is an independent predictor of mortality after femoral neck fracture and is associated with an increased rate of dislocation, revision surgery, and failure of internal fixation. Although patients with Parkinson's disease with a nondisplaced or valgus impacted femoral neck fracture may be treated with internal fixation, they are at significantly higher risk of failure of fixation compared with patients without Parkinson's disease. Use of a hemiarthroplasty through an anterolateral approach may reduce the likelihood of requiring a revision operation. Level of Evidence: Level III, therapeutic study.